EA-EDNet: encapsulated attention encoder-decoder network for 3D reconstruction in low-light-level environment - Deng, Yulin; Yin, Liju; Gao, Xiaoning; Zhou, Hui; Wang, Zhenzhou; Zou, Guofeng (Multimedia systems, 2023)
3D reconstruction via neural networks has become striking nowadays. However, the existing works are based on information-rich environment to perform reconstruction, not yet about the Low-Light-Level (LLL) environment where the information is extremely scarce. The implementation of 3D reconstruction in this environment is an urgent requirement for military, aerospace and other fields. Therefore, we introduce an Encapsulated Attention Encoder-Decoder Network (EA-EDNet) in this paper. It can incorporate multiple levels of semantic to adequately extract the limited information from images taken in the LLL environment and can reason out the defective morphological data as well as intensify the attention to the focused parts. The EA-EDNet adopts a two-stage combined coarse-to-fine training fashion. We additionally create a realistic LLL environment dataset 3LNet-12, and accompanying propose an analysis method for filtering this dataset. In experiments, the proposed method not only achieves results superior to the state-of-the-art methods, but also achieves more delicate reconstruction models.